Isoenzymatic variation in the germplasm of Brazilian races of maize (Zea mays L.) - Gimenes Marcos Aparecido; Lopes Catalina Romero (Genetics and Molecular Biology, 2000)
There are more than 200 races of maize (Zea mays L.) divided into three groups (ancient commercial races, the recent commercial races, and indigenous races). Although the indigenous races have no commercial value, they have many important characteristics which can be incorporated into maize breeding programs. Most Brazilian indigenous germplasm race stocks were collected at least 40 years ago, and nothing is known of the genetic variability present in this germplasm. The genetic variability was assayed in 15 populations from four indigenous races of maize (Caingang, Entrelaçado, Lenha and Moroti) and five indigenous cultivars, using five isoenzymatic systems encoded by 14 loci. The analysis revealed a low level of variability among the samples studied. Overall, the mean number of alleles/polymorphic locus was three, 64.3% of the loci analyzed being polymorphic and the estimated heterozygosity was 0.352. The mean number of alleles/polymorphic locus per population was 1.6. A mean of 47.5% of the loci were polymorphic. The mean expected heterozygosity was 0.195, the mean genetic identity was 0.821 and the proportion of total genetic diversity partitioned among populations (Gst) was 0.156. A founder effect could explain the low variability detected.